The trade policy review mechanism : a critical analysis - Kende, Mathias (Oxford : Oxford University Press, 2018)
The WTO's Trade Policy Review Mechanism, which reviews the trade policies and practices of each WTO member at regular intervals, is generally considered to function well. In this day and age, complacency is unwise. Examining trade policy reviews throughout the lifetime of the TPRM, this work details its evolution from Article X of the General Agreement on Tariffs and Trade to the proposed modifications resulting from the mechanism's latest appraisal, examining the budgetary capabilities and technical performance of all the main entities who participate in the reviews.
This edition previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 5, 2018).
Keywords: World Trade Organization. -- Trade Policy Review Body; Industry; Business & Management